Understanding young children's attitudes towards reading in relation to their digital literacy activities at home - Ohi, Sarah; ÖZTÜRK, GÜLŞAH (My University, 2018)
The effect of digital literacy practices upon young children's learning is a contentious and growing area for research and debate. Nowadays, children encounter many different types of texts through their everyday engagement with digital technologies. The study reported here investigated the relationships between 6 and 7-year-old children's home digital literacy practices, parental views about the use of technology and children's attitudes towards reading as perceived by the children and their parents. A total of 105 children and their parents, from two primary schools in Istanbul participated in this study. Parents completed a questionnaire about their views on the use of technology, their children's digital literacy experiences and their perceptions of their children's reading attitudes, while the children engaged in individual interviews. The results from this study indicate that children's attitudes towards reading are significantly related to both the frequency of their engagement in digital literacy activities in their homes and their parents' perception of their child's attitudes to reading. The findings suggest that parents can support children's enjoyment in reading by engaging in both digital and non-digital print experiences with their children.
Keywords: Digital Literacy; Early Childhood; Early Literacy; Family Literacy; Reading; Technology; Dijital Okuryazarlık; Erken Çocukluk; Erken Okuryazarlık; Aile Okuryazarlığı; Okuma; Teknoloji